Effect of antithyroid (Propylthiouracil PTU( on some physiological parameters in local chicks: AL-Ma'atheedi MSMS , Matty HN and AL-Kassim NAH - المعاضيدي, محمودسالم محمد شيت (The Iraqi Journal of Veterinary Medicine, 2012)
The aim of this experiment is to study the effect of antithyroid agent (propylthiouracil) (PTU) on some physiological parameters in domestic chicks. 36 local one 4 week of age day old chicks were used .chicks were distributed randomly in to three groups: (control group) fed on standard diet , while 2nd and 3rd groups were fed diet contain 0.01 and 0.1℅ of antithyroid agent propylthiouracil (PTU) respectively from 1-25 days of age . blood sample were taken from jugular vein at the end of the 4th week in order to study the effect of PTU treatment on blood picture .result revealed that PTU treatment in group treated with 0.1℅ PTU compared with control group significantly increased in red blood cell count ,Heterophils ,basophiles percentage and stress index at 4th weeks of age in group treated with 0.1℅ PTU compared with 0.01℅ PTU and control group significantly decreased in lymphocytes percentage, beside that no significant difference in total leukocytic count ,hemoglobin ,packed cell volume ,eosinophils , monocytes percentage and erythrocytes indexes in treated groups with compared group